2023
DOI: 10.1099/ijsem.0.006156
|View full text |Cite
|
Sign up to set email alerts
|

Phylotaxonomic assessment based on four core gene sets and proposal of a genus definition among the families Paracoccaceae and Roseobacteraceae

Dao-Feng Zhang,
Wei He,
Zongze Shao
et al.

Abstract: The families Paracoccaceae and Roseobacteraceae comprise metabolically, phenotypically and genotypically diverse members, and their descriptions rely heavily on 16S rRNA gene analysis. Hundreds of genera have been reported within the two families and misclassifications have been a reoccurring problem, even when the taxonomies have been established based on genome-scale phylogenetic reconstructions. In this study, we conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Genome-based phylogeny of the supermatrix approach from protein sequences of the bac120 gene set (120 single-copy genes prevalent in Bacteria ) was reconstructed by using EasyCGTree version 4.1 (https://github.com/zdf1987/EasyCGTree4) [3, 33]. The bac120 tree indicated that strains WL0004 T and XHP0148 T clustered together with R. marina CGMCC 1.9108 T and were close to the cluster formed by R. alba 1NDH52C T and R. pomeroyi DSS-3 T ().…”
Section: Genome Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Genome-based phylogeny of the supermatrix approach from protein sequences of the bac120 gene set (120 single-copy genes prevalent in Bacteria ) was reconstructed by using EasyCGTree version 4.1 (https://github.com/zdf1987/EasyCGTree4) [3, 33]. The bac120 tree indicated that strains WL0004 T and XHP0148 T clustered together with R. marina CGMCC 1.9108 T and were close to the cluster formed by R. alba 1NDH52C T and R. pomeroyi DSS-3 T ().…”
Section: Genome Featuresmentioning
confidence: 99%
“…Genome annotation was conducted by the National Center for Biotechnology Information (NCBI) Prokaryotic Genome Annotation Pipeline (PGAP) [26]. The genomes of strains WL0004 T and XHP0148 T were both reported in our previous study [3]. The complete 16S rRNA gene sequences of strains WL0004 T and XHP0148 T were predicted from the two genomes using program barrnap (version 0.9; https://github.com/tseemann/barrnap).…”
Section: Genome Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…To conduct phylogenomic analysis, genomic informations of type strains in the phylum Verrucomicrobiota were collected using Python (www.python.org) and Perl (www.perl.org) scripts (https://github.com/zdf1987/Usefull_Scripts) introduced in our previous study [37]. The assembly accession numbers were used to retrieve genomic data sets from the RefSeq and GenBak (if not available in RefSeq) databases (on 1 December 2023) through Batch Entrez (www.ncbi.nlm.nih.gov/sites/batchentrez), because genome records collected in RefSeq are all annotated using NCBI PGAP [20].…”
Section: Genome Featuresmentioning
confidence: 99%